Linking spatial characteristics of urban green space and mental well-being: green space biodiversity and landscape spatial patterns - Ha, Jaeyoung (Kansas State University, 2022)
During the past several decades, much progress has been made in the understanding of how urban green space promotes the mental well-being of urban residents. In particular, the last two decades have witnessed a growing interest in the association between the quantity of urban green space and the effect on residents’ well-being. However, little research has attempted to disentangle the linkage between the structure of urban green space and mental well-being beyond the quantity aspect. To address this question, this dissertation includes a literature review regarding restorative mechanisms influenced by the spatial characteristics of urban green space. Also, this dissertation includes experimental and observational studies: a biodiversity study and a landscape pattern study. In the biodiversity study, I examined how the biodiversity of campus green space can promote mental well-being of college students by assessing their visual and auditory perceptions of two green spaces having either low or high biodiversity. I employed a 2 by 2 study design, in which 319 students were randomly assigned to one of four treatments: (1) low biodiversity without sound, (2) high biodiversity without sound, (3) low biodiversity with sound, and (4) high biodiversity with sound. In a controlled setting, students viewed on a computer a 360-degree-view video of either a low- or high-diversity site, with or without the natural sounds at each site, that had been recorded on the Kansas State University campus (a grassy lawn area, and a native meadow garden). The restorative status and mood of students were evaluated both pre-intervention and post-intervention via a self-reported survey. The results of this study revealed that neither biodiversity level nor sound by themselves had any significant effect on the mood or restorative status of these college students. However, a significant interaction effect between the visual and auditory perceptions was found. Students who were exposed to a high-biodiversity environment with natural sound conditions were shown to have lower levels of negative mood states compared to those without natural sound conditions. In the landscape-pattern study, I explored how landscape patterns (i.e., composition and configuration) are associated with the mental health of residents in the city of Chicago. This study used mental health and socioeconomic data from a total of 6,405 residents from 61 Chicago communities in the Healthy Chicago Survey conducted by the Chicago Department of Public Health. High-Resolution Land Cover (HRLC) data were used to calculate urban green space (e.g., trees, grass, and water). Landscape metrics were quantified to measure landscape patterns, including percentage, size, distance, and aggregation of urban green space in 61 community areas across Chicago. The results of this study showed that residents who resided in urban landscapes with small water bodies and that had greater distances between forested areas (owing to the presence of several large urban parks and forests within the Chicago study area) reported less psychological distress. As for total urban green space, there was a lower level of psychological distress in landscapes with a disaggregated distribution of urban green spaces (i.e., multiple small green spaces) in comparison with a single (or a few) large green space(s). These two studies have implications for landscape design and planning to improve the mental well-being of urban residents. Using both experimental and observational studies, this dissertation is able to contribute to a better understanding of mental restoration mechanisms provided by green spaces within urban environments on both a micro (site-based) and macro (landscape) scale. Furthermore, the study can provide insights into how landscape patterns and biodiversity affect human well-being in order to find a balance between human use and the conservation of nature.
Keywords: Urban green space; Mental health; Mental well-being; Landscape pattern; Biodiversity; Restorative environment